The effect of organizational culture & job satisfaction on turn over intention, with organizational commitment as a mediating variable (study case at pt sas kreasindo utama) - Vizano, Nico Alexander; Setiyani, Aris; Nawangsari, Lenny (Jurnal Ekonomi, 2018)
Currently high levels of turnover intentions have become a serious problem for many companies, therefore it is necessary to investigate the cause of its. The cause of turn over intention should be prevented from interfering with the productivity of the company. The purpose of this study was to investigate the effect of organizational culture, employee satisfaction on turn over intention. Organisational Commitment used to mediating variable. Population of the sample from PT SAS Kreasindo utama is 230 people and 150 samples obtained using the Slovin formula. Methods of data analysis used statistical analysis with Partial List Square (PLS). The results showed that organizational culture have a positive effect on organizational commitment ,job satisfaction have a positive effect on organizational commitment, Organizational culture have a negative effect on turn over intention, Job satisfaction have a negative effect on turn over intention, Organizational Commitment have a negative effect to turn over intention, Organizational Culture has a negative and significant effect on turn over intention through Organizational Commitment and Job Satisfaction has a negative and significant effect on turn over intention through Organizational Commitment.